2015
DOI: 10.1038/ejcn.2015.192
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inulin and fructo-oligosaccharide on the prevention of acute radiation enteritis in patients with gynecological cancer and impact on quality-of-life: a randomized, double-blind, placebo-controlled trial

Abstract: Prebiotics can improve the consistency of stools in gynecologic cancer patients on RT. This finding could have important implications in the quality-of-life of these patients during treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(76 citation statements)
references
References 28 publications
1
72
0
Order By: Relevance
“…The mixed results observed may stem from the fact that many of these therapies modulate bacteria, which do not have an impact in radiation enteropathy. However, Garcia-Peris and colleagues showed in a randomized trial that the delivery of a fiber mixture containing inulin, which promotes the growth of SCFA producers such as Roseburia, improves diarrhea in patients undergoing pelvic radiotherapy, supporting our observations (44,45).…”
Section: Discussionsupporting
confidence: 82%
“…The mixed results observed may stem from the fact that many of these therapies modulate bacteria, which do not have an impact in radiation enteropathy. However, Garcia-Peris and colleagues showed in a randomized trial that the delivery of a fiber mixture containing inulin, which promotes the growth of SCFA producers such as Roseburia, improves diarrhea in patients undergoing pelvic radiotherapy, supporting our observations (44,45).…”
Section: Discussionsupporting
confidence: 82%
“…There is moderately convincing evidence that increasing, rather than reducing fibre intake during pelvic radiotherapy has beneficial effects. Two studies using dietary manipulation (60,65) and three (59,63,64) using supplements reported improved bowel symptom scores (60,65) and improvements in stool consistency and diarrhoea outcomes (59,63,64) compared with low-fibre or non-supplemented groups. In contrast, in two studies using low-fibre dietary interventions, one reported no difference in gastrointestinal symptom scores between intervention and standard care groups either during or in the post-treatment setting (61,62) whilst a further study (58) reported improved genitourinary and gastrointestinal symptoms in patients compliant with low-fibre dietary advice amongst a number of other dietary restrictions.…”
Section: Dietary Fibrementioning
confidence: 99%
“…Eight studies (57)(58)(59)(60)(61)(62)(63)(64)(65) recruiting 639 patients, comprising six RCT (57,59,(61)(62)(63)(64)(65) (including one cross-over trial (57) ) and two cohort studies (58,60) have explored the benefit of manipulating dietary and/or supplemental fibre during pelvic irradiation. Of the interventional RCT, two manipulated dietary fibre alone (60,65) , three used a fibre supplement (59,63,64) (two of which included additional dietary restrictions (59,64) ) and a further study with long-term follow-up manipulated dietary fibre in combination with a low-lactose restriction (61,62) . Seven studies (58)(59)(60)(61)(62)(63)(64)(65) explored the role of fibre in preventing gastrointestinal toxicity (i.e.…”
Section: Dietary Fibrementioning
confidence: 99%
See 1 more Smart Citation
“…Acute radiation enteritis is a clinical term characterized with edema, inflammation, ulceration, epithelial degeneration, decrease in mitotic activity and crypt abscess in gastrointestinal tract [3, 4]. In clinical practice, acute radiation enteritis are commonly occurred after two weeks of radiation, and often cause a number of intestinal symptoms such as diarrhea, defecation pain and mucus, blood in the stool, and tenesmus [5]. In contrast to acute radiation enteritis, chronic radiation enteritis are developed from acute radiation enteritis or direct exposure to local tissue ischemia and long lasting interstitial fibrosis, vascular occlusive meningitis which are caused by chronic inflammation.…”
Section: Introductionmentioning
confidence: 99%